A Rare Case of Tuberous Sclerosis with Giant Cell Astrocytoma - Sidra Masood, Mudassar Sharif Bhatti, Sidra Masood, Mudassar Sharif Bhatti (Journal of Rawalpindi Medical College, 2022)
Tuberous sclerosis complex (TSC) is a neurocutaneous disease inherited in an autosomal dominant pattern with variable penetration. This case report is of a 12-year-old boy who presented with complaints of headache, vomiting, and fits. His neurocutaneous stigmata combined with radiological imaging led us to the diagnosis of TSC with sub ependymal giant cell astrocytoma (SEGA). His family screening revealed interesting details of how the disease is running in his family. He is now scheduled for surgery at our neurosurgery department for the removal of SEGA. This case is significant because it is a typical depiction of the classic pattern of autosomal dominant inheritance of TSC with evident variable penetration within members of the same family.